Strengthening bonds through pharmily day 2022 / Ili Rabiatul Adawiah Ismail, Muhammad 'Izzuddin Zamery and Dr. Gurmeet Kaur Surindar Singh - Ismail, Ili Rabiatul Adawiah; Zamery, Muhammad 'Izzuddin; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
Pharmily Day, one of the most anticipated events of the semester, marked the end of 2022. This program was organised by the Sekretariat Mahasiswa Fakulti Farmasi (SMF) and Society of Pharmacy Students (SOPHYS) on December 21, 2022 at the FF4 corridor, Faculty of Pharmacy, Puncak Alam Campus, Universiti Teknologi MARA. Surprisingly, despite being held for the first time, this event garnered positive feedback from participants. With the slogan "Strive Together, Care For Each Other", this programme achieved its purpose of further strengthening the relationship and bridging the gap among the faculty members.